2012
DOI: 10.1590/s0104-42302012000200021
|View full text |Cite
|
Sign up to set email alerts
|

Análise comparativa do risco de quedas entre pacientes com e sem diabetes mellitus tipo 2

Abstract: There appears to be an association between hyperglycemic status and poorer mobility, with an increased fall risk even in younger patients and in those with shorter disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…This study sought to determine whether percent IntraMAT in the lower leg was different among women with and without type 2 diabetes, as IntraMAT may be one of the mediating factors responsible for the accelerated musculoskeletal aging observed in people with type 2 diabetes [ 1 ]. In agreement with other studies [ 2 , 43 , 44 ], we found that our cohort of women with type 2 diabetes had greater TUG test scores indicating poorer functional mobility, lower grip strength, and lower specific force, an indirect measure of muscle quality. Various mechanisms for poor functional mobility and strength in adults with type 2 diabetes have been proposed and include reduced muscle fibre size and number [ 45 ] and reduced α -motor neuron innervation [ 46 ]; however we hypothesized that IntraMAT might also be a likely mediator.…”
Section: Discussionsupporting
confidence: 93%
“…This study sought to determine whether percent IntraMAT in the lower leg was different among women with and without type 2 diabetes, as IntraMAT may be one of the mediating factors responsible for the accelerated musculoskeletal aging observed in people with type 2 diabetes [ 1 ]. In agreement with other studies [ 2 , 43 , 44 ], we found that our cohort of women with type 2 diabetes had greater TUG test scores indicating poorer functional mobility, lower grip strength, and lower specific force, an indirect measure of muscle quality. Various mechanisms for poor functional mobility and strength in adults with type 2 diabetes have been proposed and include reduced muscle fibre size and number [ 45 ] and reduced α -motor neuron innervation [ 46 ]; however we hypothesized that IntraMAT might also be a likely mediator.…”
Section: Discussionsupporting
confidence: 93%
“…This pathology may also cause neural and cardiovascular alterations, diabetic neuropathy, diminished visual and auditory acuity, dizziness, polypharmacy, hypoglycemia, among others [20]. In the sample researched, no significant changes in mobility were verified in the diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search yielded 131 potential articles; 68 were MVC-related and 63 were fall-related injuries which were reviewed for inclusion. The study included original articles based on hospital data; ten MVC-related[ 15 16 17 18 19 20 21 22 23 24 ] and nine falls-related articles[ 25 26 27 28 29 30 31 32 33 ] were considered for analysis. The study population in MVC-related studies was mainly drivers in which the driving impairment caused by diabetic complications was addressed.…”
Section: Methodsmentioning
confidence: 99%